Computer-Aided Exergy Sensibility Analysis of Nitrobenzene Production through Benzene Nitration Using an Acid Mixture - Tamy Herrera-Rodríguez; Lina S. Miranda-Jiménez; Ángel D. González-Delgado (International Journal of Chemical Engineering)
Nitrobenzene is widely produced via benzene nitration to be applied in several industries such as pharmaceutical, textile, and agricultural. In this work, an exergy sensibility analysis was performed with the aim of identifying possible opportunities of process improvements. The irreversibilities, exergy of wastes, and efficiency were calculated per stage through exergy balance. The simulation software Aspen plus V10.1 provided the physical exergies of process streams while chemical exergies were found in literature. A sensibility analysis was also carried out in order to study the effect of efficiency of some stages (polyfunctional reaction and cooling 1) on global exergy efficiency. This analysis reveals that nitrobenzene production from benzene is an efficient process from an exergy viewpoint (88%). The total irreversibilities, total exergy of wastes, and exergy of utilities-inlet were calculated in 41,647,341.85 MJ/h, 5,537,487.3 MJ/h, and 18,137,363.71 MJ/h, respectively. The results obtained from sensibility analysis suggested that heat flow of heat exchangers HE-201, HE-303, and HE-301 could provide energy requirements for heating.